Students’ Involvement Analysis towards Teachers’ Teaching Reflection and Its Impact on Classroom - Maman Asrobi; Muhammad Adib Nazri; Zordi Wirawan Asroful Hakim; Selamet Riadi Jaelani (LPPM Universitas Bumigora Mataram, 2023)
Analyzing students' involvement in teachers' teaching reflection can offer valuable insights into the effectiveness of classroom instruction. By encouraging students to participate in the reflection process, teachers can gain a better understanding of their strengths and areas for improvement. This study aimed to investigate students' involvement in teachers' teaching reflection and its impact on classroom. The participants of this study were 20 students of Madrasah Tsanawiyah NW Sikur. This study used qualitative descriptive research approach. There are two sorts of data sources in qualitative research: primary resources and secondary resources. The result revealed that students generally responded positively to being involved in teachers' teaching reflection. In conclusion, the analysis of students' involvement in teachers' teaching reflection and its impact on the classroom highlights the significant role students can play in shaping effective teaching practices and fostering a conducive learning environment.